Genetic heterogeneity in childhood leukemia/lymphoma: a Turkish cohort with strong predisposition - Onder, Gizem; Ozdemir, Ozkan; Taylan, Fulya; Canpolat, Cengiz; Yalcin, Koray; Erbey, Fatih; Sozmen, Banu Oflaz; Asarcikli, Fikret; Bayhan, Turan; Akcabelen, Yunus Murat; Yarali, Nese; Ozbek, Namik Yasar; et al. (Frontiers in Genetics, 2025)
BackgroundLeukemia is the most common cancer in children, and 10%–15% of patients with leukemia/lymphoma carry pathogenic germline cancer-predisposing variants. Identifying these variants is critical for understanding the genetic predisposition and optimizing clinical management.MethodsWe performed germline short-read sequencing in 36 individuals from 20 families with suspected leukemia/lymphoma predisposition, including 20 index cases, 9 affected relatives, and 7 unaffected members.ResultsWe identified 13 clinically relevant germline variants in known cancer predisposition genes including TP53, ETV6, MSH6, MLH1, and BRCA1. Notably, we uncovered novel candidate variants in ATR, TNFRSF9, ETAA1, and KSR1, which was supported by segregation analysis, consanguinity patterns, and secondary malignancy phenotypes. Several index cases exhibited striking familial cancer syndromes involving both hematologic and solid tumors, with progression from ALL to AML or glioma. Deep clinical–genomic correlation enabled reclassification of variants and refined diagnostic and therapeutic decision-making in multiple cases. The patients were referred to genetic counseling for surveillance of carriers and risk assessment for various family members.ConclusionThese findings emphasize the clinical utility of germline testing in pediatric hematologic cancers by providing novel insights into the predisposition to leukemia/lymphoma and contributing to treatment regimens, donor selection, and diagnostic refinement, particularly in populations with high consanguinity.